Acute severe asthma treated by mechanical ventilation: 10 years' experience from a district general hospital. Issue 6 (June 1986) - Luksza, A R; Smith, P; Coakley, J; Gordan, I J; Atherton, S T
Abstract : A retrospective study was made of patients requiring mechanical ventilation (intermittent positive pressure ventilation--IPPV) for acute severe asthma in a district general hospital during 1974-83. Thirty two patients required IPPV on 34 occasions. Complications included pneumothorax in six (18%) patients, chest infection in 12 (35%) patients, pulmonary collapse in three (9%) patients, hypotension at induction of IPPV in 12 (35%), and gastrointestinal bleeding in three (9%). Three (9%) patients died. Therapeutic bronchial lavage was performed in 19 patients. The procedure produced a rise in effective static compliance from a mean of 17 (SD 6) ml/cm H2O to 24 (9) ml/cm H2O at four hours. Bronchial lavage was associated with a significant excess of respiratory infections. A feature common to most patients was undertreatment before admission to hospital.